Optimal mileage-based PV array reconfiguration using swarm reinforcement learning - Zhang, Xiaoshun; Li, Chuanzhi; Li, Zilin; Yin, Xueqiu; Yang, Bo; Gan, Lingxiao; Yu, Tao (Energy conversion and management, 2021)
•A new optimal mileage-based PV array reconfiguration (OMAR) is constructed.•The OMAR can maximize the total benefit instead of only the generation benefit.•The OMAR decomposition with two sub-problems reduces the optimization difficulty.•The swarm reinforcement learning is used to obtain high-quality optimums of OMAR.•The proposed method can obtain higher total benefit than 6 comparative algorithms. This paper constructs a new optimal mileage-based PV array reconfiguration (OMAR) in a PV power plant under partial shading conditions. It aims to maximize the power output of a PV power plant, and minimize the additional capacity and mileage payments resulting from the power fluctuation in a performance-based frequency regulation market. To reduce the optimization difficulty of OMAR, it is decomposed into two optimization sub-problems, including an upper-layer discrete optimization of PV array reconfiguration and a lower-layer continuous optimization of real-time generation scheduling. The upper-layer discrete optimization is addressed by the proposed swarm reinforcement learning (SRL), which can implement an efficient exploration and exploitation with multiple cooperative agents instead of a single learning agent. The rest lower-layer optimization is handled by the fast interior point method. The proposed method’s effectiveness is thoroughly evaluated on the 10 × 10 total-cross-tied PV arrays under various partial shading conditions. Simulation results demonstrate that the proposed SRL can obtain a larger total benefit than genetic algorithm (GA), particle swarm optimization (PSO), grasshopper optimization algorithm (GOA), harris hawks optimizer (HHO), butterfly optimization algorithm (BOA), and Q-learning, in which the benefit increment can reach from 2.12% (against PSO) to 10.62% (against Q-learning).